CUSTOMER PERCEPTION ON THE OVERALL QUALITY OF SERVICE DELIVERED A CASE STUDY OF THE ELECTRICITY COMPANY OF GHANA (ECG) - Mansaray, Abdul Karim; Lapkoff, Dr. Monica; Little, Anthony (American Journal of Supply Chain Management, 2021)
Purpose: The purpose of this study was to ascertain customer perception on the overall quality of service delivered by ECG Methodology: The study adopted an explanatory research design in order to achieve the study objectives. The population for this research was made up of the employees of ECG and the customers of ECG, who were systematically sampled. Data was then analyzed through descriptive statistics using the Statistical Package for Social Science. The study employed descriptive statistics, multivariate data analysis as well as regression models Results: The study found out that customers perceived the quality of services being offered by the energy company as unsatisfying. Unique contribution to theory, practice and policy: To improve service quality, ECG would have to isolate the dimensions that were noted to be weak; being empathy and responsiveness. These may be addressed by professional training and retraining front line personnel and technical rapid response teams to address the concerns of customers with urgency and a human face